Improving Students Speaking Skill through Role Play at Seventh-Grade Students - Patricia Diona; Yahmun Yahmun (Journey: Journal of English Language and Pedagogy, 2024)
The aim of this research was to improve the speaking skill of seventh grade students at SMP Bhakti Malang by using Role Play. This was because the result of preliminary research showed that students faced difficulties in speaking English as a foreign language they had to learn . The instruments used in this research were interviews, observation sheets, questionnaires and tests. The findings showed that 81.25% students reached the school Minimum Passing Grade (MPG). The results of this research indicated that the application of role play method could improve students’ speaking skill is claimed to be successful.